2021
DOI: 10.1007/s00421-021-04673-w
|View full text |Cite
|
Sign up to set email alerts
|

Daily 30-min exposure to artificial gravity during 60 days of bed rest does not maintain aerobic exercise capacity but mitigates some deteriorations of muscle function: results from the AGBRESA RCT

Abstract: Purpose Spaceflight impairs physical capacity. Here we assessed the protective effect of artificial gravity (AG) on aerobic exercise capacity and muscle function during bed rest, a spaceflight analogue. Methods 24 participants (33 ± 9 years, 175 ± 9 cm, 74 ± 10 kg, 8 women) were randomly allocated to one of three groups: continuous AG (cAG), intermittent AG (iAG) or control (CTRL). All participants were subjected to 60 days of six-degree head-down tilt bed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 44 publications
5
25
0
Order By: Relevance
“…The present results indicated that the impact of iAG was stronger in the anteroposterior plane, as demonstrated by smaller changes in CoP displacement, velocity, and frequency sway parameters than identified for the control group. Our observations may partially confirm the results of Kramer et al (32), which showed moderate preservation of the function of the plantar flexor muscles in the current HDT bed rest by use of the AG protocols. This is congruent with our results for the anteroposterior direction, as the plantarflexor muscles make the primary contribution to balance control in this direction (21).…”
Section: Intermittent Ag Prevents Decline In Some Balance Variables After 60-day Hdt Bed Restsupporting
confidence: 91%
See 1 more Smart Citation
“…The present results indicated that the impact of iAG was stronger in the anteroposterior plane, as demonstrated by smaller changes in CoP displacement, velocity, and frequency sway parameters than identified for the control group. Our observations may partially confirm the results of Kramer et al (32), which showed moderate preservation of the function of the plantar flexor muscles in the current HDT bed rest by use of the AG protocols. This is congruent with our results for the anteroposterior direction, as the plantarflexor muscles make the primary contribution to balance control in this direction (21).…”
Section: Intermittent Ag Prevents Decline In Some Balance Variables After 60-day Hdt Bed Restsupporting
confidence: 91%
“…This is congruent with our results for the anteroposterior direction, as the plantarflexor muscles make the primary contribution to balance control in this direction (21). Unlike our data, Kramer et al did not detect any differences between the two AG protocols (32), which suggests plantar flexor muscle strength does not fully explain iAG effects. In our study, iAG mitigated the deleterious effects of HDT bed rest on sway displacement, sway velocity, and sway power spectra, particularly in conditions with eyes closed and standing on an unstable surface (see Table 1 for details).…”
Section: Intermittent Ag Prevents Decline In Some Balance Variables After 60-day Hdt Bed Restsupporting
confidence: 90%
“…HDBR studies have examined the effects of artificial gravity applied via centrifugation as a potential countermeasure for spaceflight-associated brain and behavioral changes ( Frett et al, 2020 ). Recent data shows that artificial gravity does not prevent aerobic capacity declines during bed rest, although it does mitigate some muscular function decay ( Kramer et al, 2021 ) and partially counteract upright balance ( De Martino et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subjects experienced a radial force of 2 g on the foot level and 1 g on the centre of mass. A more detailed description of the countermeasure can be found elsewhere (Kramer et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%